Responding to global development challenges: views from Brazil and India - Oliver Stuenkel (Deutsches Institut für Entwicklungspolitik (DIE), 2010)
Brazil and India are undergoing profound transformations as they become global actors. As their international engagement increases, they nevertheless continue to possess characteristics common to other developing countries. Forty million Brazilians and 300 million Indians live under the poverty line, representing more than one third of the world's poor. Against this backdrop, Brazil's and India's emergence and their views on addressing global development challenges have important implications for international development policy. Brazil's and India's ascendance will create changes in two areas. First, as emerging powers, they will seek greater weight in international development institutions. This may alter the way those institutions operate. Second, as increasingly prominent donors, Brazil's and India's role raises questions about their impact on development procedures established by the Western-dominated Development Assistance Committee (DAC). Brazil and India, increasingly engaged in both their respective regions and in Africa, are attempting to differentiate themselves from traditional donors. This study analyses both countries' motivations and strategies as rising actors in the multilateral context and as emerging bilateral donors, evaluates the potential impacts their presence will have on development policy, and points to opportunities for European actors to engage with both Brazil and India.
Keywords: 330